(3GdOQ GdfVjQ aj BOGH GdhRjQs - (3GdZfjej , LGO Gddg Gdajhej GdTGaYj, CHh GdGNdGU,J (B1101 (3g` s
(3ChdgG (B:s
(3gPg ahGFO MSGf hfcGJ ai ZGjI GdHjGf , JJYdb HefUH GdhRGQI GdSfi , hGdcSH ef QhM QjMGfg GdLfi LYdgG NOeI dCMO hRQGA GdOhdI GdYKeGfjI HeUQ s
(3hQJHgG GdeDda Ydi ebOeI hebUOjf hNGJeIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B105 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B107s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B22 - (3U (B550 s
Keywords: (3GdSjGSI hGdGLJeGYs